variability of stomatal sensitivity to leaf water potential across tree species indicates a continuum between isohydric and anisohydric behaviours - Klein, Tamir; Niu, Shuli (Functional ecology, 2014)
The relationship between stomatal conductance (gₛ) and leaf water potential (Ψₗ) is key to the understanding of plant function under changing climate. The variability among tree species gave rise to selection towards either of two contrasting water management types: isohydric or anisohydric. This study explores the variability of gₛ to Ψₗ across tree species. Curves of gₛ(Ψₗ) were collected from the scientific literature for 70 woody plant species. The data set is comprised of angiosperm and gymnosperm species from all major forest biomes. The hypothesis that curves from different tree species diverge between isohydric and anisohydric behaviours was tested. Species‐specific curves formed a continuum, rather than dichotomy between isohydric and anisohydric, as confirmed by distribution models. Alternatively, the water potential at 50% of the maximum gₛ (Ψgₛ50) was used to quantitatively compare between species. A major difference emerged among xylem anatomy classes whereby ring‐porous species had higher absolute gₛ at Ψₗ < −2 MPa than diffuse‐porous and coniferous species. A positive, linear correlation was shown between Ψgₛ50 and Ψₗ at 50% loss of xylem conductivity. The results suggest that stomatal sensitivity to leaf water potential strongly relates to xylem characteristics. The use of Ψgₛ50 offers a quantitative alternative to the current, yet biased, distinction between isohydric and anisohydric species.